2020
DOI: 10.3390/agronomy10091427
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Chitosan Oligomers–Amino Acid Conjugate Complexes against Fusarium culmorum in Spelt (Triticum spelta L.)

Abstract: Fusarium head blight (FHB) is a complex disease of cereals caused by Fusarium species, which causes severe damages in terms of yield quality and quantity worldwide, and which produces mycotoxin contamination, posing a serious threat to public health. In the study presented herein, the antifungal activity against Fusarium culmorum of chitosan oligomers (COS)–amino acid conjugate complexes was investigated both in vitro and in vivo. The amino acids assayed were cysteine, glycine, proline and tyrosine. In vitro t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…The EC 90 values attained with a COS−ε-polylysine conjugate (507.5, 580.2 and 497.4 µg•mL −1 for N. parvum, D. seriata and B. dothidea, respectively [33]) were better than those attained in this work for the COS−Tyr conjugate (1021.4, 672.1 and 707.7 µg•mL −1 , respectively), but-from an economic perspective-the latter formulation would be much more viable (given that the price of ε-polylysine is much higher than that of tyrosine: 245 €/100 mg vs. 58 €/100 g). An additional advantage of the COS-Tyr formulation could be its versatility as a crop protection product: EC 50 and EC 90 values against Fusarium culmorum (320 and 1107 µg•mL −1 , respectively) were of the same order of magnitude as those reported herein [37].…”
Section: Comparison Of the Efficacy Of The Treatmentssupporting
confidence: 66%
See 1 more Smart Citation
“…The EC 90 values attained with a COS−ε-polylysine conjugate (507.5, 580.2 and 497.4 µg•mL −1 for N. parvum, D. seriata and B. dothidea, respectively [33]) were better than those attained in this work for the COS−Tyr conjugate (1021.4, 672.1 and 707.7 µg•mL −1 , respectively), but-from an economic perspective-the latter formulation would be much more viable (given that the price of ε-polylysine is much higher than that of tyrosine: 245 €/100 mg vs. 58 €/100 g). An additional advantage of the COS-Tyr formulation could be its versatility as a crop protection product: EC 50 and EC 90 values against Fusarium culmorum (320 and 1107 µg•mL −1 , respectively) were of the same order of magnitude as those reported herein [37].…”
Section: Comparison Of the Efficacy Of The Treatmentssupporting
confidence: 66%
“…As regards the mode of action of the conjugate complex, it may be the result of an enhanced additive fungicidal effect per se, and/or via a concurrent action on diverse fungal metabolic sites. In a previous work [37], we also hypothesized that conjugation of COS and Tyr increases the cationic surface charge of COS, enhancing the linkage (through electrostatic interactions) to the negatively charged site-specific binding receptors on the fungal membrane.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
“…Nonetheless, it was suggested that it might be the result of an enhanced additive antimicrobial effect, per se, and/or via a concurrent action on diverse microbial metabolic sites. An increase in the cationic surface charge of COS may also result from conjugation with phytochemicals, which would enhance the linkage to negatively charged site-specific binding receptors on the bacterial/fungal membranes [ 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that it may be the result of an enhanced additive fungicidal effect per se, and/or via a concurrent action on diverse fungal metabolic sites. The conjugation with phytochemicals may increase the cationic surface charge of COS, enhancing the linkage (through electrostatic interactions) to the negatively charged site-specific binding receptors on the fungal membrane [28,[64][65][66].…”
Section: Antifungal Activitymentioning
confidence: 99%